Analisis Probabilitas Risiko dan Usulan Perbaikan Pada Proses Weaving Pembuatan Produk Handuk di PT Paberik Tekstil Kasrie Menggunakan Metode Fuzzy-Bow Tie Analysis - Al Masruroh, Eki Wulandari; Tranggono, Tranggono (BRILIANT: Jurnal Riset dan Konseptual, 2025)
The research aims to identify the risks that occur in the weaving process and provide risk management and prevention strategies. The method of this research is to use fuzzy-bow tie analysis where fuzzy analysis is used to calculate the probability of factors and impacts that occur while bow tie analysis is to identify risk variables and plan management and prevention strategies. The findings from the study have identified five risk variables: fire, work fatigue, Operator accident, machine damage, and product defect. After conducting a survey of 5 employees working in the weaving department by measuring the probability of risk occurrences and the level of risk impact, the results were that of the 5 main risks identified, 3 of them had high risk values and 2 had moderate risk. To reduce the level of risk, risk mitigation is carried out by conducting an analysis of prevention and management strategies using the Bow tie method.